Visuomotor adaptation in martial arts and running experts - Werner, S.; Hasegawa, K.; Kanosue, K.; Vogt, T. (Annual conference of the section martial arts and martials sports of the German Association of Sport Science, Belgium, 2018)
For martial artists it is essential to adapt previously learned techniques to various situations and opponents. This type of motor learning, where an already existing motor behavior is al-tered, is called visuomotor adaptation. Previous studies found involvement of the prefrontal cortex, among other brain structures, in adaptation (Taylor and Ivry 2014; Werner et al. 2014). Furthermore, martial arts experts show increased gray matter volume in this very brain area compared to endurance athletes (Schlaffke et al. 2014). These results suggest that martial arts training leads to improved visuomotor adaptation compared to running train-ing. The present study aims at investigating this hypothesis.